Impact of the Construction of the Aral Sea on Central Asian Countries - Erkin Xaliqulov (Academia One Publishing, 2023)
In this article, there is an opinion about the aggravation of the severe ecological situation that is happening today in the areas along the Aral Sea, the deterioration of the ecological situation, the toxic salts that have accumulated at the bottom of the Aral Sea due to the processes of degradation and desertification, etc. held
Keywords: Aral Sea; degradation; desertification; biosphere